Imaging Secondary Electron Emission from a Single Atomic Layer. Issue 4 (15th January 2021) - Dyck, Ondrej; Swett, Jacob L.; Lupini, Andrew R.; Mol, Jan A.; Jesse, Stephen
Abstract: Graphene‐based devices hold promise for a wide range of technological applications. Yet characterizing the structure and the electrical properties of a material that is only one atomic layer thick still poses technical challenges. Recent investigations indicate that secondary‐electron electron‐beam‐induced current (SE‐EBIC) imaging can reveal subtle details regarding electrical conductivity and electron transport with high spatial resolution. Here, it is shown that the SEEBIC imaging mode can be used to detect suspended single layers of graphene and distinguish between different numbers of layers. Pristine and contaminated areas of graphene are also compared to show that pristine graphene exhibits a substantially lower SE yield than contaminated regions. This SEEBIC imaging mode may provide valuable information for the engineering of surface coatings where SE yield is a priority. Abstract : Operando prototype graphene devices are examined with a scanning transmission electron microscope. Secondary electron e‐beam induced current (SEEBIC) is used to detect a single layer of graphene and distinguish different layer numbers. SEEBIC imaging offers a complementary view into electrical conductivity and connectivity with high spatial resolution.